Periodismo investigativo y el desarrollo cultural en la Radio Unika 93.5 fm, cantón Quevedo año 2021 - Vera Alava, Erika Vanessa (2021)
In this investigative process, it was carried out in order to analyze the impact that investigative journalism has on cultural development on Radio Unika 93.5 FM in the Quevedo city, we based ourselves especially on the behavior that people adopt when receiving certain information. The present research was carried out based on a sample of the audience of said media, using as the main tool a virtual survey applied to a total a 100 people, which contrasted the different points of view of the users, which helped by segmenting their answers, leading us toward the rise of the problem, letting us know what would be the proposals that would improve this deficiency. Through the surveys established, it was obtained as a result that the audience of this communication medium considers that the participatory role it has in society is very important and influential, since from this specific town or society it acquires certain behaviors in the face of the information it receives.